PENINGKATAN MOTIVASI BELAJAR MELALUI MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) PADA PESERTA DIDIK KELAS IV SDN PUTAT JAYA IV/380 SURABAYA - Pingky Nur Andryani; Meilantifa; Nurul Aini (CV. Adiba Aisha Amira, 2025)
This research aims to examine the improvement in students' learning motivation by applying the Team Game Tournament (TGT) learning model in the Indonesian Language subject, specifically on figurative language material, for fourth-grade students at SD Negeri Putat Jaya IV/380 Surabaya. The research was motivated by the observed lack of student engagement and motivation in learning activities. Using a Classroom Action Research (CAR) approach, this study was conducted in Class IV-B, involving 22 students. Data were collected through questionnaires and direct observation during the learning process. The questionnaire responses were then analyzed using descriptive quantitative methods. The study was carried out in two cycles, each consisting of four stages. The results indicated a significant increase in student motivation, with an improvement of 6% from Cycle I (80%) to Cycle II (86%). This percentage demonstrates that the learning motivation of Class IV-B students falls into the high category, affirming the effectiveness of the Team Game Tournament model in enhancing engagement in Indonesian language lessons.